Association Analysis Of Gender, Job Type, Education Level, Income Level, Religion And Spirituality Levels Against The Type Of The Selected Bank Community In Indonesia - Bakri, Adzan Noor (MALIA: Journal of Islamic Banking and Finance, 2019)
This study aims to analyze and explore the relationship of demographic aspects of society, including gender, education level, income level, occupation, religion, and spiritual level towards the types of banks that used by the people of Indonesia. The research method used is descriptive quantitative method with  correspondence analysis technique.  200 communities have been chosen as a sample. They are the customers of conventional banks, sharia banks, or  both of them. The results of this study argue  that, not all demographic aspects of society have association or relationship with the type of bank selected by respondents. Only religion and spiritual level aspects have real associations. Muslim respondents are more likely to choose Islamic banks than non-multifarious respondents. Respondents with high spiritual level tend to be associated with sharia banks rather than low ones. This research can be used for the marketing designer as one of the basic determines for the marketing strategy of the bank.